Best Answer

Write the statement as an algebraic equation. Then solve the equation.

Twice a number: 2x

Three times the number: 3x

One third the number: x/3

In your question, you said: 2x - 3x = x/3 + 14

Multiply each side by 3 ==> 6x - 9x = x + 42

Combine the terms on the left side ==> -3x = x + 42

Subtract 'x' from each side==> -4x = 42

Divide each side by -4 ==> x = 42/(-4) = -21/2

x = -10.5

Q: How do i solve twice a number minus three times the number is equal to one third the number plus fourteen?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

To solve the problem 5 - -6, think of it as 5 + 6. You can do this because two negative numbers equal as positive number, and similarly two negative signs equal a positive. Therefore 5 --6 is 11.

You cannot solve log x- 2 unless (i) log x - 2 is equal to some number or (ii) x is equal to some number.

90

A number to a negative power is equal to One divided by number to its positive power. So, x^-2 is equal to 1/x2.

You solve this by dividing 60,000 by 105, then multiplying the number you get by 100.

Related questions

You don't. There's no question there, and nothing that needs solving. If it were equal to something, then we could find what number 'x' must be.

To solve the problem 5 - -6, think of it as 5 + 6. You can do this because two negative numbers equal as positive number, and similarly two negative signs equal a positive. Therefore 5 --6 is 11.

it depends what you want to do with it...if the number is x,then it is2x - 3=

It can't be solved because the discriminant of this quadratic equation is less than zero

There's nothing there to solve, because no statement is made. If all of that were equal to something, then we could get some exercise figuring out what 'x' must be to make it a true statement. But in its present form, it doesn't say anything. It's just a number that depends on what 'x' is.

I put the larger number above the smaller number and then I subtract. 719 423 ----- 296

You cannot solve log x- 2 unless (i) log x - 2 is equal to some number or (ii) x is equal to some number.

Sobtract 1 from minus 9 and get minus 10.

-96 = 33-y -96-33 = -y -129 = -y y = 129 Remember a minus divided into a minus is equal to a plus.

Using the quadratic formula, you should get two answers: 1 + sqrt(14) and 1 - sqrt(14).

The question contains an expression but not an equation. You cannot solve an expression.

you need to find out what can you multiply by 5 minus 2 will equal 13. so x=3